Dangerous bodies, matter and emotions: public assemblies and embodied resistance. Issue 3 (2nd September 2017) - Lilja, Mona
Abstract: Departing from Judith Butler's ground-breaking book Notes toward a Performative Theory of Assembly, this article will explore why extra cultural meaning is attached to resisting bodies that are involved in demonstrating assemblies. Across the globe resistance is played out by bodies that occupy pavements, streets and squares. The participants in public assemblies, are taking part in various emotional processes while coming together to struggle against, for example, disenfranchisement, effacement and abandonment. In embodied, coordinated actions of resistance the gathering itself signifies something in excess of what is being said at the event; there is a distinction between forms of linguistic performativity and forms of bodily performativity. By bringing in the concepts of emotions and matter, this paper will explore how and why resisting bodies signify something else/more than the vocalised or linguistic demands that they are making.